Effects of a quaternary lidocaine derivative, QX-314, on the respiratory activity in brainstem-spinal cord preparation from newborn rats. (21st April 2016) - Takahashi, Kenichi; Hayakawa, Chikara; Onimaru, Hiroshi
Highlights: QX314 is a membrane-impermeable quaternary derivative of lidocaine. QX314 may selectively inhibit nociceptors but there is concern about toxicity. We examined the effects of this drug on respiratory activity. Extracellular application of 200 μM QX314 depressed C4 inspiratory activity. Our findings may explain the central toxicity after systemic application of QX314. Abstract: In the clinical setting, the use of QX-314 (a quaternary derivative of lidocaine) has been proposed to achieve the selective inhibition of nociceptors that express transient receptor potential vanilloid 1 (TRPV1) channels with fewer motor deficits. However, it has been also reported that QX-314 may produce systemic CNS toxicities with relative potencies that are approximately twice as high as those of lidocaine. There are no reports concerning the effects of extracellular QX-314 on the rhythm-generating neurons in the respiratory center. In the present study, we examined the effects of QX-314 on respiratory rhythm generation in brainstem-spinal cord preparations from newborn rats. The extracellular application of QX-314 (200 μM) decreased the C4 burst rate, amplitude and slope during the initial rising phase, and the effects slowly developed with a half-decay time of approximately 20 min. The combined application of capsaicin (10 or 100 μM) with QX-314 (100 μM) showed no additional effect. The intracellular application of QX-314 (100 μM) to respiratory neurons depressed the action potentials with a half-decay time of around 5 min. Our findings could explain one of the mechanisms underlying the central toxicities that occur after the systemic application of QX-314.